Cost Analysis of Mountain Schools in Nepal: Comparison of Earthquake Resistant Features in Rubble Stone Masonry vs. Concrete Block Masonry - Schildkamp, Martijn; Araki, Yoshikazu (Frontiers in Built Environment, 2019)
This paper analyzes the cost breakdown of earthquake resistant schools in Kaski District of Nepal, as built by Smart Shelter Foundation. Three types of designs are compared, which are rubble stone masonry with a wooden roof structure, and concrete block masonry with either a wooden roof or with a steel trussed roof. An in-depth cost analysis and cost comparison was carried out, based on a unique collection of local building prices from 19 different villages, as well as generally applicable District Rates, all spanning a period of 10 years between 2007 and 2017. Master Estimates were divided into the 5 main building phases of foundation, walls, roof, floor and finishing, and then further broken down into local costs for materials, labor and transportation. These cost comparisons give a detailed insight in the distribution of the costs, the pricing of individual materials and construction elements, the effect of price fluctuation on the total costs, and the cost implications of different solutions for seismic measures. It is concluded that the market prices, especially of locally sourced materials, fluctuate too much, making it impossible to detect useful patterns for general application or future predictions. Also, no similarities were found between the local village rates versus the general District Rates, which insufficiently reflect variations at the micro level, such as availability of materials, site accessibility, or local preferences. To address these issues, the paper introduces a helpful tool for rapid cost estimation of different school designs. The last chapter analyzes the price implications of adding or removing certain seismic features. It concludes that improving masonry with cement mortar has the highest cost impact, but that inclusion of important seismic features such as horizontal bands, buttresses and steel bars is not that expensive, meaning there is basically no financial obstacle to incorporate these in new constructions of schools and houses. However, all interventions require in-depth technical and scientific validation, for which the authors have started an initiative named SMARTnet. The paper ends with an appeal to experts and academics worldwide, to exchange their knowledge and to support the project with their time and expertise.